Advancing photopolymerization and 3D printing: High-Performance NiII complexes bearing N2O2 Schiff-base ligands as photocatalysts - Pesqueira, Naralyne M. [UNESP]; Morlet-Savary, Fabrice; Schmitt, Michael; Carvalho-Jr, Valdemiro P. [UNESP]; Goi, Beatriz E. [UNESP]; Lalevée, Jacques (Elsevier, 2024)
New high-performance photocatalysts based on metal structures are being developed for polymerization. However, using low-cost metals while ensuring effectiveness is challenging. In this study, two NiII complexes NiL1 and NiL2 were synthesized using N2O2 Schiff-base ligands bearing π-extended rings (naphthaldehyde (H2L1) and phenylsalicylaldehyde (H2L2) groups), respectively. These complexes were characterized by FTIR, UV–Vis and 1H NMR spectroscopy, elemental analysis, cyclic voltammetry, and MALDI-TOF mass spectrometry. NiL1 and NiL2 were evaluated in photoinitiating system as new photocatalysts for the Free Radical Photopolymerization of Ethoxylated (3) Trimethylolpropane Triacrylate (TMPETA) for violet and green light. Three-component systems were employed in the presence of Di-tert-butyl-diphenyl iodonium hexafluorophosphate (Iod) and ethyl dimethylaminobenzoate (EDB). The absorption, luminescence, and redox properties of nickel complexes and ligands were explored and compared for a better understanding of their structure/reactivity relationship. The designed nickel complexes showed good photoinitiation abilities. NiL2 exhibited the highest monomer conversion, and it was investigated in the on–off process under green light irradiation, demonstrating the efficiency of the system in reactivating the polymerization process. An oxidative pathway mechanism was proposed based on free energy, steady state photolysis and electron spin resonance spin trapping experiments. The best system was successfully applied in cationic photopolymerization and 3D printing.
Keywords: 3D printing; Free radical photopolymerization; Nickel complex; Photochemistry; Schiff-base